The Impact of Career-Related Self-Efficacy and Parent-Child Career Goal Congruence on Career Engagement among University Student - Rayhan Tsarwah Rizky; Arini Widyowati (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2026)
This study aimed to examine the influence of career – related self-efficacy and parent- child goal congruence as predictors of career engagement among university students. The participants comprised 237 active students (17.7% male, 82.9% female) aged 19-21 (M = 19.23, SD = .97), selected from the Faculty of Psychology at a private university in Yogyakarta, Indonesia. The study adopted a quantitative method with three instruments such as the career-related self-efficacy, the parent-child career goal congruence, and the career engagement scales. Furthermore, the data obtained were analyzed using multiple linear regression analysis. The results showed that career – related self – efficacy and parent – child career goal congruence significantly predicted career engagement, accounting for 19.6% of the variance. This suggested that students who possessed higher self-efficacy and stronger congruence between career goal and parental expectation were associated with increased career engagement. In conclusion, the study provided valuable insights for parents and counselors in supporting students’ career engagement.